Application of Reflector in OTDR Test and Diagnosis System of PON Network - Chengbin Shen; Zhe Du; Ming Jiang; Bo Wang (Dianxin kexue)
A mathematic model was built-up to analyze ODN attenuation event detection in OTDR system of PON, and then combining the mathematic analysis and experimental result, the application value and necessity of wavelength-selective reflector in PON optical link test and diagnosis system were investigated. Based on operators' requirements, several implementations of reflector were proposed and analyzed, and technical requirements for reflector were given. Finally, the international and domestic standardization progress of reflector was introduced.